Nutrition Paradox: Severe Acute Malnutrition Amidst the Proliferation of Processed Foods in Bilaspur’s Tribal Region in Chhattisgarh, India - Kimberley D’Souza; Naveen Ramesh (Indian Journal of Public Health)
Despite India’s overall economic growth and targeted antimalnutrition efforts, certain districts in Chhattisgarh, exhibit high severe acute malnutrition (SAM) rates, at 17.4% in 2022 per NFHS-5 data. We retrospectively studied four SAM-affected children, finding common factors: maternal malnutrition, poverty, recurrent infections, poor child-rearing knowledge, inadequate birth spacing, and the use and dependence on processed foods. The prevalence of these foods alongside declining traditional feeding practices highlights a “Nutrition Paradox.”